Pathological features of reinnervated skeletal muscles after crush injury of the sciatic nerve in ob/ob mice. Issue 3 (13th July 2021) - Asano, Takahiro; Tsujii, Masaya; Iino, Takahiro; Odake, Kazuya; Sudo, Akihiro
Abstract: Introduction/Aims: Obesity is a factor contributing to suboptimal improvement of motor function in peripheral nerve disorders. In this study we aimed to evaluate the skeletal muscles during denervation and reinnervation after nerve crush injury in leptin‐deficient (ob/ob) mice. Methods: Experiments were performed on the skeletal muscles of the hindlimbs in 20 male ob/ob mice and controls. Characteristics of the gastrocnemius muscles were evaluated by histological analysis, immunohistological analysis, and Sircol‐collagen assay after measurement of body weight and wet weight of the skeletal muscles, and by walking track analysis. The sciatic nerve was denervated by crushing with smooth forceps and reinnervation was evaluated. Results: Gastrocnemius wet weight was significantly lower in the ob/ob mice than in the control mice. A smaller cross‐sectional area of type II fibers and increase of type I fiber grouping of the skeletal muscles was demonstrated in the ob/ob mice. After nerve injury, motor function recovery was equal between the groups but the cross‐sectional area of type II fibers was significantly smaller in the ob/ob mice than in control mice at 4 weeks. The denervated muscles showed an increase in collagen deposition in the interstitial space; predominant in the ob/ob mice after nerve injury. Discussion: The results of this study suggest that fibrosis in the skeletal muscle of obese patients after nerve injury is prominent, which may impair improvement of muscle function after treatment of peripheral nerve disorders.